Targeting ERK enhances the cytotoxic effect of the novel PI3K and mTOR dual inhibitor VS-5584 in preclinical models of pancreatic cancer - Ning, Changwen (Oncotarget, 2017)
Pancreatic ductal adenocarcinoma (PDAC) is a deadly disease in urgent need of newer therapeutic modalities. Majority of patients with PDAC have mutations in KRAS, which unfortunately remains an ineffectual target. Our strategy here is to target KRAS downstream effectors PI3K and mTOR. In this study, we investigated the antitumor efficacy of the novel PI3K and mTOR dual inhibitor VS-5584 in PDAC. Our data shows that PI3K/mTOR dual inhibition causes ERK activation in all tested PDAC cell lines. Although the MEK inhibitor GSK1120212 could abrogate VS-5584-induced ERK activation, it did not substantially enhance cell death in all the cell lines tested. However, combination with ERK inhibitor SCH772984 not only mitigated VS-5584-induced ERK activation but also enhanced VS-5584-induced cell death. In a xenograft model of PDAC, we observed 28% and 44% tumor inhibition for individual treatment with VS-5584 and SCH772984, respectively, while the combined treatment showed superior tumor inhibition (80%) compared to vehicle control treatment. Our findings support the clinical development of VS-5584 and ERK inhibitor combination for PDAC treatment.